Optimalisasi Hasil Jagung melalui Pemupukan dan Penggunaan Varietas Unggul pada Lahan Kering di Bawah Tegakan Kelapa - Aji, Himawan Bayu; Suwitono, B.; Hidayat, Y.; Lala, Fredy (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Approximately 80% of the land under the stands of coconut trees has the opportunity for intercropping. Corn farming under coconut stands can increase the efficiency of land use and provide additional income to farmers. One of the determinants of the success of increasing crop production is through balanced and fertilization rational and the use of superior varieties. The study aims to determine the effect of type, dose, and time of fertilization of corn on dry land under coconut stands. The study was conducted from June to October 2018 in Bumi Restu Village, Wasile District, East Halmahera Regency. The results showed that maize production in 40% shade conditions under coconut stands was influenced by the variety and fertilization, but only one variable interacted namely dry shelled weight.. Corn production on dry land under coconut stands achieved by the four varieties (Variety Nasa 29, Sukmaraga, Bhishma, and Lamuru) are as follows; 5.5 tons/ha; 4.7 tons/ha; 5.3 tons/ha and 5.2 tons/ha at a dosage of organic fertilizer 2.000 kg/ha,NPK Phonska 450 kg/ha, and urea 150 kg/ha. The Bisma and Lamuru varieties are shade tolerant and can be grown on dry land under the stands of coconut.